Barriers and Facilitators to Cochlear Implant Uptake in Australia and the United Kingdom. Issue 2 (March 2020) - Bierbaum, Mia; McMahon, Catherine M.; Hughes, Sarah; Boisvert, Isabelle; Lau, Annie Y. S.; Braithwaite, Jeffrey; Rapport, Frances
Abstract : Objectives: Hearing loss (HL) affects a significant proportion of adults aged >50 years by impairing communication and social connectedness and, due to its high prevalence, is a growing global concern. Cochlear implants (CIs) are effective devices for many people with severe or greater sensorineural HL who experience limited benefits from hearing aids. Despite this, uptake rates globally are low among adults. This multimethod, multicountry qualitative study aimed to investigate the barriers and facilitators to CI uptake among adults aged ≥50 years. Design: Adult CI and hearing aid users with postlingual severe or greater sensorineural HL, general practitioners, and audiologists were recruited in Australia using purposive sampling, and a comparative sample of audiologists was recruited in England and Wales in the United Kingdom. Participants were interviewed individually, or in a focus group, completed a demographic questionnaire and a qualitative survey. Data were analyzed using thematic analysis. Results: A total of 143 data capture events were collected from 55 participants. The main barriers to CI uptake related to patients' concerns about surgery and loss of residual hearing. Limited knowledge of CIs, eligibility criteria, and referral processes acted as barriers to CIs assessment referrals by healthcare professionals. Facilitators for CI uptake included patients' desire for improved communication and social engagement, and increased healthcare professional knowledge and awareness of CIs. Conclusions: There are numerous complex barriers and facilitators to CI uptake. Knowledge of these can inform the development of targeted strategies to increase CI referral and surgery for potential beneficiaries. Abstract : Supplemental Digital Content is available in the text.